Color discrimination in the tufted capuchin monkey, Sapajus spp. - Paulo Roney Kilpp Goulart; Daniela Maria Oliveira Bonci; Olavo de Faria Galvão; Luiz Carlos de Lima Silveira; Dora Fix Ventura (PLoS ONE, 2013)
The present study evaluated the efficacy of an adapted version of the Mollon-Reffin test for the behavioral investigation of color vision in capuchin monkeys. Ten tufted capuchin monkeys (Sapajus spp., formerly referred to as Cebus apella) had their DNA analyzed and were characterized as the following: one trichromat female, seven deuteranope dichromats (six males and one female), and two protanope males, one of which was identified as an "ML protanope." For their behavioral characterization, all of the subjects were tested at three regions of the Commission International de l'Eclairage (CIE) 1976 u'v' diagram, with each test consisting of 20 chromatic variation vectors that were radially distributed around the chromaticity point set as the test background. The phenotypes inferred from the behavioral data were in complete agreement with those predicted from the genetic analysis, with the threshold distribution clearly differentiating between trichromats and dichromats and the estimated confusion lines characteristically converging for deuteranopes and the "classic" protanope. The discrimination pattern of the ML protanope was intermediate between protan and deutan, with confusion lines horizontally oriented and parallel to each other. The observed phenotypic differentiation confirmed the efficacy of the Mollon-Reffin test paradigm as a useful tool for evaluating color discrimination in nonhuman primates. Especially noteworthy was the demonstration of behavioral segregation between the "classic" and "ML" protanopes, suggesting identifiable behavioral consequences of even slight variations in the spectral sensitivity of M/L photopigments in dichromats.